2007
DOI: 10.1111/j.1365-3059.2006.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PCR test to detect the downy mildew causal agent Plasmopara halstedii in sunflower seeds

Abstract: Plasmopara halstedii, the causal agent of downy mildew of sunflower, is an obligate parasite but viable sporangia and oospores of the pathogen may be found in a quiescent state in seeds of sunflower and therefore may be transported with sunflower seeds in international commercial exchanges. In order to prevent the spread of this pathogen, especially the introduction of potentially new races, an efficient method to analyse sunflower seed samples is required. In this study, a P. halstedii-specific polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…(Phan et al, 2002;Konstantinova et al, 2002;Guillemette et al, 2004;Ioos et al, 2007). In this study, the use of a commercial kit to extract DNA from maize seeds was shown to be efficient as no influence on the DNA extraction was observed.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…(Phan et al, 2002;Konstantinova et al, 2002;Guillemette et al, 2004;Ioos et al, 2007). In this study, the use of a commercial kit to extract DNA from maize seeds was shown to be efficient as no influence on the DNA extraction was observed.…”
Section: Resultsmentioning
confidence: 86%
“…the internal transcribed spacer regions (ItS) of the rDNA have been widely used to differentiate and to detect closely related fungal species (Phan et al, 2002), as they are highly conserved parts of the genome within the same species and are variable among species (Lovic et al, 2002;Lee et al, 2002). Based on those regions, different primers have been designed and successful applications of them are reported for detection and identification of several target organisms (Lee et al, 2002;Iacomi-Vasilescu et al, 2009;Konstantinova et al, 2002;Rios et al, 2007;Ha et al, 2009;Consolo et al, 2009 andIoos et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…X. strumarium) to cultivated sunflower and supports Sackston's (1992) theory of the North American origin of sunflower downy mildew. Most likely the export of unnoticed contaminated seeds (Meliala et al 2000;Ioos et al 2007) gave rise to the worldwide distribution of sunflower downy mildew.…”
Section: Host Range and Distribution Of Sunflower Downy Mildewmentioning
confidence: 98%
“…Roeckel-Drevet et al (1999) generated an oligonucleotide primer for the selective amplification of P. halstedii, Bouterige et al (2000) employed an enzyme linked immunosorbent assay (ELISA) test, and Spring and Haas (2004) were successful with fatty acid patterns as markers of infected vs. healthy sunflower seeds. Recently, Ioos et al (2007) developed a method for the direct detection of the pathogen in seed samples based on the ribosomal large sub unit DNA. Though their test was able to detect a near 1:50 ratio of seed contamination, this was not practical, probably because of the problem of representative sampling.…”
Section: Detection Risk Assessmentmentioning
confidence: 99%
“…Aegerter et al 2002;Hukkanan et al 2006). A particular field of interest is the identification of seed contamination with pathogenic oomycetes for which successful approaches have been published for the downy mildew pathogens of basil (Belbahri et al 2005) and sunflower (Thines et al 2004;Ioos et al 2007). Molecular diagnostic tools were also revealed to be useful in isolate differentiation of sunflower downy mildew (Intelman and Spring 2002;Spring et al 2006;Delmotte et al 2008) and oomycete populations of Plasmopara viticola (Furuya et al 2009) and…”
Section: Introductionmentioning
confidence: 98%